Evaluation of training projects based on socio-training: the case of the Quality Control project - Espinoza-Guano, Mónica (2022)
Currently, training projects are a necessary instrument for teacher planning, so that expected learning must be focused on the reality of the context in which students develop. The purpose of this study is to establish the learning outcomes in a clear and concrete way according to the socio-training approach, under which the learning outcome and the product resulting from it must provide a solution to a problem of the context. The methodology applied was focused on action-training research so that through the analysis and evaluation processes of expected learning, changes or improvements can be made to the Quality Control training project. The main results show that most of the expected learning is somewhat theoretical and does not contribute to the solution of a real problem. By improving the training project, the learning results are intended to be of a practical nature, contributing to the improvement of the community's living conditions. The quality control training project was improved to a great extent, through the planning of the teacher's activities, autonomous and practical; the contents were structured according to the socio-training approach, so that the students deal with real cases of their context.